Non-linear fitting-based phasor measurement method for PMU calibrator. (March 2019) - Liu, Hao; Xu, Sudi; Bi, Tianshu; Martin, Kenneth E.; Qian, Cheng; Wang, Lu
Highlights: A non-linear fitting-based phasor measurement method for PMU calibrator is proposed. Parameters setting methods are proposed to ensure uniqueness of the solution. White noise restraining methods are proposed to further improve accuracy. A PMU calibrator is developed based on the proposed method. Testing results show that he PMU calibrator can provide valid test references. Abstract: With the increasing penetration of renewable energies, phasor measurement units (PMUs) play increasingly important roles in security control and mechanism studies for power systems. The testing and calibration of PMUs are key to their effectiveness in a power system; therefore, providing valid test reference values with sufficient precision under steady-state and dynamic conditions is critical. This paper proposes a non-linear fitting-based phasor measurement method for a PMU calibrator to provide reference measurements. Two universal phasor-fitting models are built to represent different signals in PMU steady and dynamic testing. An objective function is presented, which obtains the minimum value of the sum of squares of a non-linear real-valued function based on phasor-fitting models. The methods to set the initial points and bound constraints of the parameters to be fitted are stated to make the objective function convex. An iterative technique, finding the local minimizer of the built objective function in the restricted region, is proposed to calculate the phasor, frequency, and rate of change of frequency (ROCOF). A white noise restraining method is proposed to further improve measurement accuracy. Then, the proposed method is implemented into hardware to develop a real PMU calibrator. To verify the accuracy of the PMU calibrator, simulations and experimental testing are carried out. Results show that the effectiveness of the PMU calibrator can meet calibration requirements under typical static and dynamic conditions of power systems with high penetration of renewable energies. The developed PMU calibrator can thus be used to calibrate PMUs.